Case report: Lower eyelid Reconstruction with the rotation flap pedicled by orbicularis oculi muscle - Duan, Mengying; Yue, Chao; Peng, Jianzhong (Frontiers in Surgery, 2022)
Background Loss of eyelid tissue can be caused by trauma, congenital defects or tumors. Eyelid reconstruction is complicated and challengingly difficult because of the complex anatomy of the eyelid. Several types of surgical procedures for the reconstruction of eyelid defects are available. Objective To describe reconstruction of lower-eyelid defects using a rotation flap pedicled by the orbicularis oculi. Methods Fourteen patients (mean age = 67 years old; ages range of 53–86 years old) who suffered from tumor excision from the lower eyelid were treated by the method. Results The mean duration of follow-up was 14 (range, 12–16) months. Ectropion, abnormal eyelid position and donor-site morbidity were not observed during follow-up. Conclusion A rotation flap pedicled by the orbicularis oculi can be a good choice for single-stage reconstruction of lower-eyelid defects.